2013
DOI: 10.1021/jf4034943
|View full text |Cite
|
Sign up to set email alerts
|

Compost Maturity Assessment Using Physicochemical, Solid-State Spectroscopy, and Plant Bioassay Analysis

Abstract: The vermicompost produced from flower waste inoculated with biofertilizers was subjected to compost maturity test: (i) physicochemical method (pH, OC, TN, C:N); (ii) solid state spectroscopic analysis (FTIR and (13)C CPMAS NMR); and (iii) plant bioassay (germination index). The pH of vermicompost was decreased toward neutral, C:N ratio < 20; reduced organic carbon with increased nitrogen indicates the compost attains maturity. The final vermicomposts result shows reduction of complex organic materials into sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…In cattle manure composts, alkyl-C first decreased, and then increased to a stable level in the curing stage, similar to the findings by Tang et al [19], Gómez et al [20] and Wang et al [9]. In addition, alkyl-C in chicken manure composts generally increased as composting proceeded, coinciding with the results of Gómez et al [20, 21] but inconsistent with those of Spaccini and Piccolo [22]. The increase of alkyl C may be attributed to the preservation of CH 2 groups in long-chain paraffin structures [28], methylene groups in aliphatic rings and chains [29], and long-chain aliphatic bio-polyesters [30, 31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In cattle manure composts, alkyl-C first decreased, and then increased to a stable level in the curing stage, similar to the findings by Tang et al [19], Gómez et al [20] and Wang et al [9]. In addition, alkyl-C in chicken manure composts generally increased as composting proceeded, coinciding with the results of Gómez et al [20, 21] but inconsistent with those of Spaccini and Piccolo [22]. The increase of alkyl C may be attributed to the preservation of CH 2 groups in long-chain paraffin structures [28], methylene groups in aliphatic rings and chains [29], and long-chain aliphatic bio-polyesters [30, 31].…”
Section: Discussionsupporting
confidence: 88%
“…Increased alkyl C/O-alkyl C ratios were reported from cattle composts during composting [19]. Kumar et al [21] evaluated the compost maturity of mixed flower waste vermicompost inoculated with biofertilizer by 13 C CP/MAS NMR, and found greater aliphatic C than aromatic C. Spaccini and Piccolo [22] indicated that the compost maturity was characterized by a decrease of alkyl components based on 13 C NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Initial wastes were characterized by a broad hydrogen bonded O H stretch at 3328 cm −1 , strong aliphatic methylene peaks at 2921 and 2852 cm −1 , aldehydes and organic esters peak at 1739 cm −1 , C O stretch of amides at 1633 cm −1 , a slight amine peak at 1366 cm −1 , an intense C O stretch of polysaccharides, cellulose and hemicelluloses peak at around 1034 cm −1 . A slight peak was also observed at 787 cm −1 which was attributed to C O stretching of carbonate and silica (Deka et al, 2011;Gupta and Garg, 2009;Kumar et al, 2013).…”
Section: Ft-ir Analysismentioning
confidence: 98%
“…The increase in GI can be due to the progress of decomposition of organic substrates and reduction of phytotoxic elements resulting from vermicomposting process. Kumar et al (2013) studied the effect of …”
Section: Biological Evaluation Of Vermicompost Maturity Seed Germinatmentioning
confidence: 99%